Developing sports tourism based on local wisdom in Gorontalo: Potentials, challenges, and strategic directions - Pakaya, Rosbin; Datau, Suriyadi; Tumaloto, Ella H; Kadir, Sulasikin Sahdi; Aliriad, Hilmy (UIR Press, 2025)
Background: Sports tourism based on local wisdom offers an alternative approach to tourism development that strengthens cultural identity and enhances destination uniqueness. However, research that explicitly integrates sports tourism with local wisdom—particularly in Gorontalo—remains limited, creating a gap in understanding how traditional cultural practices can be incorporated into sports tourism strategies. Objectives: This study aims to examine the potential benefits and challenges of developing sports tourism grounded in local wisdom. Methods: An exploratory qualitative approach was employed, in-depth interviews were conducted with a number of informants (n = 18), observations, documentation reviews, and focus group discussions (FGDs) with three key stakeholder groups: local communities, local government institutions, and tourism industry actors. Data were analyzed using the interactive model of Miles and Huberman and validated through source and methodological triangulation. Findings/Results: Qualitative findings reveal that Gorontalo people continue to preserve cultural traditions such as bowling balls, boat racing, and lumense dance which is the main attraction of sports tourism. The region's strengths include its rich cultural heritage, natural resources suitable for outdoor sports, and active community participation. However, development is hindered by limited infrastructure, weak promotional efforts, and insufficient financial support. Conclusion: Strategic development requires cross-sector collaboration, strengthened community capacity, and innovation in sports-tourism products rooted in local wisdom. Practically, these insights can guide the creation of inclusive and sustainable tourism initiatives that leverage Gorontalo’s cultural and natural assets.